SPREAD SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN SYARIAH YANG LISTED DI BEI - Santoso, Budi (Jurnal Ilmiah Akuntansi Indonesia, 2019)
Abstract: This study aims to analyze the spread of stock spreads before and after the stock split and dividend distribution in sharia food and beverage companies listed on the Indonesia Stock Exchange. A sample of 11 companies was selected by purpossive sampling. This study used the incidence period 5 days before and 5 days after stock split and dividend distribution with descriptive statistic analysis technique, normality test (Shapiro Wilk test), and hypothesis test (Paired t Test). Descriptive statistical results show that stock spreads before and after stock splits and dividend payouts each have different mean values. However, the result of hypothesis testing with Paired T Test shows that there is no difference of stock spread before and after stock split and dividend distribution found no differenceKeywords: stock spread, stock split, dividend distribution